‘Promising Spaces’: universities’ critical-moral mission and educative function - McLean, Monica (University of the Western Cape, 2015)
Attention has been drawn to reduction of universities’ purposes to serve economic interests only. This dissatisfaction has provoked thinking about how to reclaim a critical, moral role for universities in society. Inspired by contemporary utopian studies this paper brings together traditional ideas about how transmitting university knowledge connects to universities’ critical-moral functions, Amartya Sen and Martha Nussbaum’s capabilities approach adapted for education, and Basil Bernstein’s theories about knowledge distribution. Focusing on the educative function, the aim is to develop a theoretically-informed and practical vision of a university education which is both personally transformative and able to produce critical citizens and workers. Research evidence from two projects on university education reveals ‘promising spaces’ (Cooper, 2014) in which to realise these aims. I conclude that there is reason to believe that the transmission and acquisition of knowledge and understanding in specific fields is key to preserving and recreating a critical-moral mission for universities wherever they are in the world, even though current conditions are inclement and unequal.